2010
DOI: 10.1159/000320486
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Stromal Cell Transplantation Attenuates Cognitive Dysfunction due to Chronic Cerebral Ischemia in Rats

Abstract: Aims: This study was aimed to elucidate if bone marrow stromal cells (BMSC) could ameliorate cognitive dysfunction due to chronic cerebral ischemia when transplanted into the brain. Methods: The BMSC were harvested from green fluorescence protein (GFP)-expressing mice. Wistar rats were subjected to bilateral common carotid artery (CCA) ligation. The BMSC (4 × 105 cells) or vehicle were stereotactically injected into the right striatum 24 h after the insult. Cognitive function was evaluated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…Pathophysiological mechanism of post-stroke cognitive impairment is quite complicated [ 30 ]. However, recent studies have shown that the engrafted BMSCs may contribute to improve cognitive function in rodent models of chronic cerebral ischemia, although the underlying mechanisms are still unclear [ 10 ]. Indeed, both the BMSCs and non-Muse cells significantly increase the correct choice and decrease the error choice at 28 days after transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathophysiological mechanism of post-stroke cognitive impairment is quite complicated [ 30 ]. However, recent studies have shown that the engrafted BMSCs may contribute to improve cognitive function in rodent models of chronic cerebral ischemia, although the underlying mechanisms are still unclear [ 10 ]. Indeed, both the BMSCs and non-Muse cells significantly increase the correct choice and decrease the error choice at 28 days after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…For the decades, numerous numbers of studies have indicated that the transplanted BMSCs enhance motor function recovery after the insults in animal models of various neurological disorders, including cerebral infarct [ 3 , 6 9 ]. They also have the potential to ameliorate cognitive dysfunction under certain conditions in diffuse axonal injury and chronic cerebral ischemia models [ 10 , 11 ]. However, there are many variables that may affect the efficacy of BMSC transplantation in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…The QD800‐labeled BMSC were stereotactically or intravenously transplanted at 7 days after the onset of permanent MCA occlusion. In the intracerebral group ( n = 8), the QD800‐labeled BMSC were stereotactically transplanted into the right striatum, as reported previously 16,19–25 . Briefly, the animals were anesthetized under the above‐mentioned conditions.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are few reports on the combination of the two different neuroprotective strategies for the treatment of cerebral ischemia. Coupled with the other manuscript demonstrating its neuroprotective role on ischemic stroke[ 20 23 ], it is strongly suggested that combination of BMSCs transplantation and MH can significantly reduce infarction size and improve functional recovery by promoting neurogenesis and angiogenesis, which may be a beneficial treatment for cerebral ischemia.…”
Section: Discussionmentioning
confidence: 98%